(untitled) (American Journal of Islam and Society, 1994)
Introduction Contemporary social theory is conventionally addresed from within the dominant tradition of inquiry. Rarely is it subject to a critical reflection from beyond its own ken. This is a pity, for the subject matter and scope of social theory go beyond the confines of any exclusive tradition, while its reach and influence in the global context of our times merely reinforce its extended compass. Given the fact that the ambitious claims made by social theorists about the univetsality of their project are hardly borne out by the reality, any pretensions at exclusivism or hegemony would be as anachronistic as they are morally reprehensible. The gap between the legitimate ambitions for a universally relevant social theory and the mdity of a field grounded in its historical coflstral.l lt sand cultural prejudices can be filled only by a critical and constructive initiative taken from within the profession to constitute a candid, open, and reflexive self-encounter. The opportuneness for such an initiative is enhanced by its urgency: the discrepancies that follow on the ineptitude of our social knowledge can only raise doubts about the relevance of our science to our social condition. In deploring the tesulting ineptitude and irrelevance, it is possible to do so in the voice of a genemlized subject, the universal "I," for surely this is one of the ateas of convergence where scholats from different traditions could agree. The measure of this agreement can only be gauged by remembering that "a science for the study of society" originally went beyond its grounding in scientific reason to its justification in a moral reasoning. And here, regardless of the grounding of that morality, we find another significant area of convergence for scholars working in different ...